Evaluation of Rainfall Intensities and Erosion Index Values for Soil Conservation - Bhatia, K. S.; Singh, R. S. (Indian Forester, 1976)
Rainfall data for the twenty years period from non-recording raingauge and fifteen years period from syphon type automatic raingauge for Rehmankhera, Lacknow has been analysed in this paper for rainfall intensities for various duration, estimation of extreme probable maximum rainfall, erosion index values and their correlation with soil loss, so that data is readily available for soil conservation works. Expected maximum rainfall intensities for different duration and recurrence interval have been calculated so that peak rate of runoff is predicated by putting the value of I in the runoff equation Q = CIA. The probable yearly maximum rainfall has been found as 1726 mm. The erosion index values bave been found as 219,318 and 404 for 2,5 and 10 years frequency respectively, The mean monthly EI values have also been calculated. Erosion-index distribution curve has been prepared to indicate erosion hazards at various stages of crop growth and EI values have been correlated with soil loss.